A questionnaire-based study on knowledge and attitude towards counterfeit medication among the doctors in tertiary care hospital - Yadav, Vijay; Budania, Navin; Mondal, Arka; Kumar, Naveen; Kumar, Ritesh; Kumar Bhardwaj, Vinod; Kumar Chhockra, Vijay; Garg, Nadish; Punia, Aditi; Sharma, Priyamvada (International journal of basic and clinical pharmacology, 2018)
Background: Counterfeit drugs are a global problem and suffered almost all developing and developed countries worldwide. In India, it is a major problem which results life threatening issues as well as financial loss on health system. So, we conducted a cross sectional questionnaire-based study on knowledge and exposure to counterfeit drugs of doctors at SHKM Govt. Medical College, Nuh, Haryana, India.Methods: A structured questionnaire was distributed to 100 registered doctors. The questionnaire was based on knowledge, attitude and its consequence on the heath system by the practices of counterfeit medication.Results: There were Twenty questionnaires excluded from the study due to incomplete information. Only 57.77% (46/80) subjects having the knowledge of questionnaire correct meaning of counterfeit drug. However, almost 90% (72/80) subjects were aware about its dangerous effects. More than 50% of the subjects have suggested that modern technology is capable to control counterfeiting of the medicine.Conclusions: Counterfeit drugs create a people health hazard and waste to consumer income. The proper knowledge, awareness and modern technological approaches are the devices may helpful in diminution of counterfeit medication practices.